2012
DOI: 10.1002/mabi.201100419
|View full text |Cite
|
Sign up to set email alerts
|

Nanomaterials for Ocular Drug Delivery

Abstract: Efficient drug delivery to the eye remains a challenging task for pharmaceutical scientists. Due to the various anatomical barriers and the clearance mechanisms prevailing in the eye, conventional drug delivery systems, such as eye drop solutions, suffer from low bioavailability. More invasive methods, such as intravitreal injections and implants, cause adverse effects in the eye. Recently, an increasing number of scientists have turned to nanomaterial-based drug delivery systems to address the challenges face… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
133
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 165 publications
(133 citation statements)
references
References 102 publications
0
133
0
Order By: Relevance
“…In order to overcome these problems and increase ocular drug bioavailability, several strategies including the preparation of viscous solutions, micro/nanoparticles and hydrogels have been developed and investigated [1,4,[7][8][9][10]. In the case of viscous solutions, numerous studies have demonstrated that they do not possess sufficient mechanical strength to resist the ocular clearance mechanism, and offer only a transient improvement in ocular residence time [11,12]. On the other hand, it has been reported that the capability of drugs to penetrate across the cornea can be significantly improved by decreasing the particle size using nanoparticles [3,9,[13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…In order to overcome these problems and increase ocular drug bioavailability, several strategies including the preparation of viscous solutions, micro/nanoparticles and hydrogels have been developed and investigated [1,4,[7][8][9][10]. In the case of viscous solutions, numerous studies have demonstrated that they do not possess sufficient mechanical strength to resist the ocular clearance mechanism, and offer only a transient improvement in ocular residence time [11,12]. On the other hand, it has been reported that the capability of drugs to penetrate across the cornea can be significantly improved by decreasing the particle size using nanoparticles [3,9,[13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Durasite consists of polymeric matrix as drug carrier and so used as a vehicle for delivery of small molecules to the target efficiently. Visudyne ® is an intravenous liposomal formulation containing photosensitizer, verteporfin, in photodynamic therapy for predominantly classic subfoveal choroidal neovascularization due to AMD, pathologic myopia or presumed ocular histoplasmosis [20].…”
Section: Literature Review Novel Drug Delivery Systemsmentioning
confidence: 99%
“…14) Cyclodextrins (CDs) have been adapted as drug carriers in eye drops since they can stabilize drugs, reduce ocular irritation, enhance drug solubility and increase permeability. 15) The following mechanisms of CD-drug complexes account for these advantages. CDs pack the lipophilic drugs in their cave and deliver the cargo through the aqueous tear fluid to the eye surface with the help of their hydrophilic outer surface.…”
Section: )mentioning
confidence: 99%